Differential contribution of pyramidal cells and interneurons to activity-dependent gene transcription changes - Salar, Seda; Guhathakurta, Debarpan; Marx Hofmann, Lena (Journal of Neurophysiology, 2019)
The type of neuronal activity determines the outcome of gene expression. Hence, the characterization of underlying mechanisms in transcriptome alterations may serve as a biomarker and provide new intervention methods for the treatment of pathologic conditions. Parrish et al. (Parrish RR, Codadu NK, Racca C, Trevelyan AJ. J Neurophysiol 120: 2358-2367, 2018) show that the changes in interneuronal gene transcription are correlated with the type of the activated neuronal population and that the initiation route of Ras/ERK MAPK pathway determines the polarity of the gene expression.
CRIS-Team Scopus Importer:2019-12-10
Keywords: 0 Mg2+; 4AP; activity-dependent gene expression; Gad1; Pvalb